Exploring the Enhanced Optical and Antibacterial Properties of Ag-Doped CdWO4 Nanopowders: Synthesis, Characterization, and Multifaceted Applications - Nooshin Heydarian Dehkordi; Morteza Raeisi; Sanaz Alamdari (Nanochemistry Research)
In this research, CdWO4 (CWO) and Ag-doped CWO (Ag: CWO) nanopowders were synthesized using the easy, quick, and cost-effective co-precipitation method, considering the wide application of tungstate compounds in optoelectronics, the optical capabilities of noble metal nanoparticles (NPs), and the problems of the crystal growth process. The structural and optical properties of the prepared nanopowders were thoroughly investigated. XRD results verified the production of both nanopowders with monoclinic (wolframite) crystal structures. The lattice parameters, crystallite size, and lattice strain of both CWO and CWO: Ag nanopowders were compared using Rietveld refinement and Williamson-Hall (W-H) analysis. The presence of Ag dopant was confirmed by the observed decrease in the intensity of the vibrational mode of ν1 (Ag) at 896 cm-1 in the CWO: Ag Raman spectrum. FE-SEM and TEM images showed that Ag ions increased the size of CWO NPs and introduced some nanorods with a diameter of approximately 29 nm. Photoluminescence (PL) measurements at 2 excitation wavelengths and Ion Beam-Induced Luminescence (IBIL) results revealed that the shallow level of Ag+ dopant near the conduction band of WO66- enhanced its luminescence properties under UV (λ exc=280nm) and ion beam (E=2.2 MeV) excitations. Antibacterial analyses revealed that CWO: Ag nanopowders eliminated over 99.9% of Gram-negative bacteria Escherichia coli (E. coli) in 6 hours. Based on the results, CWO: Ag nanopowder has great potential in laser technologies, spectroscopy, medicine, and E. coli sensors.